Methods-in-Place: "Art Voice" as a Locally and Culturally Relevant Method to Study Traditional Medicine Programs in Manitoulin Island, Ontario, Canada. Issue 5 (23rd December 2015) - Barwin, Lynn; Shawande, Marjory; Crighton, Eric; Veronis, Luisa
A collaborative research project with Noojmowin Teg Health Centre on Manitoulin Island, Ontario, examined the impacts of traditional medicine workshops on participants' perceptions of culture, health, and environment. Methods used in this research turned out to be as revealing as the results themselves. This article examines how geography and the social, physical, and affective elements of place inform research methodology and challenges the idea that qualitative methods can be applied generically irrespective of the context. While researchers reflect on the role of (social) place in influencing the research process and results, we argue that the place of research should also be taken into account to adopt and develop methodologies and data collection methods that are locally and culturally relevant. We discuss how "art voice" was a highly appropriate method in a community that has a rich history and contemporary culture of visual art. This article contributes to the growing movement toward seeking culturally relevant, community-based decolonizing methods, particularly in the context of Indigenous health research.